Transformerless Photovoltaic Inverter for Photovoltaic Power Generation in Perlis to Run High AC Load - Muhammad Irwanto Misrun (School of Electrical System Engineering, 2012)
This thesis presents the transformerless photovoltaic (PV) inverter for PV power generation in Perlis to run high AC load. This study involves the data collection of solar radiation and temperature.